PENGENALAN COMPUTATIONAL THINKING PADA PESERTA LATIHAN KADER MUDA IPNU-IPPNU KECAMATAN BUNGAH KABUPATEN GRESIK - Effindi, Muhamad Afif (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
Latihan Kader Muda or LAKMUD is a term for member training of Ikatan Pelajar Nahdlatul Ulama (the Nahdlatul Ulama Student Association abbreviated as IPNU) and Ikatan Pelajar Putri Nahdlatul Ulama (the Nahdlatul Ulama Girls Student Association abbreviated as IPPNU). One of the goals of LAKMUD is to train and enhance member’s skill on problem solving, through Scientific Problem Solving. This goal has relevance with Computational Thinking. This article reports on implementation of training in Computational Thinking for LAKMUD participants. The method for the training consists of preparation and implementation of the training. The result of the training is participants could arrange steps to solve problems using the Computational Thinking approach.